Definiowanie demokracji w doktrynie Kościoła katolickiego - Kamińska, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Throughout the history of the Church a profound change in the assessment of democracy has taken place, from utter condemnation to apparent recognition. The Vatican only supports democracy which is based on Christian values. The institution of the Church is to be the authority to establish these values. Following John XXIII, the Vatican Council repeated that public authority could not act against the order settled by God. Thus the power of state authorities in this respect has been subjected to the directives of the Catholic Church. One can assume then that the political system proposed by the Church is a particular modification of feudalism. It should be ascertained that freedom – meaning the freedom of choice – expressed by individual participation in government and, consequently, in the enacted law, remains absent from the doctrine of the Catholic Church.